Entanglement between microwave fields and squeezing of the optical output field in an opto-magnomechanical ring cavity - Jinhao Jia; Juan Huang; Fengxuan Zhang; Mei Zhang (Scientific Reports)
Abstract We propose a scheme to generate entanglement between microwave fields and achieve strong squeezing of the optical output field in an opto-magnomechanical ring cavity. The system consists of two elastic yttrium iron garnet crystals with attached mirror pads inside two separate microwave cavities, and an extra fixed mirror outside the microwave cavities is utilized to complete the optical ring cavity with the two mirror pads. A magnon mode supported by the yttrium iron garnet crystal couples directly to the microwave cavity mode via magnetic dipole interaction and couples indirectly to the optical cavity mode via magnomechanical displacement, which is caused by magnetostrictive interaction and also couples the magnon mode to a phonon mode. A squeezed light is fed into the ring cavity to entangle the two phonon modes. To activate the beam splitter interaction, each magnon mode and optical cavity mode is driven by a strong red-detuned driving field. Consequently, the stationary entanglement between the two microwave cavities is obtained. The transfer efficiency of the entanglement is $$41%$$ . To ensure the squeezing of the magnon mode generated by magnetostrictive interaction transferred into the optical field, we remove two microwave cavities. The squeezing of the optical output field can reach up to $$\sim \!\! 30$$ dB at 10 mK and survives up to an environmental temperature about 500 mK. Our scheme may find various useful applications in quantum wireless fidelity network and the enhancement of sensitivity of measurements.